2021
DOI: 10.15414/jmbfs.2020.9.5.960-964
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Barrier and Structural Properties of Whey Protein Isolate-Based Films Treated by Microbial Transglutaminase

Abstract: Nowadays, polymers obtained from edible resources such as polysaccharides and proteins have attained growing consideration to substitute petroleum-derived polymers. Edible films are a good alternative for the plastic packaging since these films are biodegradable, environmental-friendly and non-toxic. However, protein based edible films have poor water permeability and lower mechanical strength. In this study, edible films based on whey protein isolate (WPI) were produced with different microbial transglutamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The properties of films were unaffected except their color [29] Whey protein concentrate/nanocrystalline cellulose Mechanical properties enhancement [30] Whey protein isolate Improved mechanical properties, gas permeability, and morphology properties [31] Quinoa protein/chitosan Enhanced thermal stability and tensile strength. Elongation at break reduction [32] Nigella sativa seed proteins Improved mechanical and barrier properties Table 1.…”
Section: Protein-based Film Type Mtgase Effect On the Films References Bitter Vetch Proteins/mesoporous Silica Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…The properties of films were unaffected except their color [29] Whey protein concentrate/nanocrystalline cellulose Mechanical properties enhancement [30] Whey protein isolate Improved mechanical properties, gas permeability, and morphology properties [31] Quinoa protein/chitosan Enhanced thermal stability and tensile strength. Elongation at break reduction [32] Nigella sativa seed proteins Improved mechanical and barrier properties Table 1.…”
Section: Protein-based Film Type Mtgase Effect On the Films References Bitter Vetch Proteins/mesoporous Silica Nanocompositementioning
confidence: 99%
“…Bitter vetch proteins/mesoporous silica nanocomposite Decrease in mechanical properties and decrease in gas permeability [24] Grass pea protein Films more resistant and digested to a less extent under gastrointestinal physiological conditions [25] Coconut protein/guar gum Enhancement of physico-chemical properties, such as mechanical, barrier properties and thermal features [26] Two quinoa varieties/chitosan Enhancement of edible film physical properties [27] Collagen fiber/casein, keratin or SPI Improved structure stability and packaging characters [28] Whey protein/heat ultrasounds The properties of films were unaffected except their color [29] Whey protein concentrate/nanocrystalline cellulose Mechanical properties enhancement [30] Whey protein isolate Improved mechanical properties, gas permeability, and morphology properties [31] Quinoa protein/chitosan Enhanced thermal stability and tensile strength. Elongation at break reduction [32] Nigella sativa seed proteins Improved mechanical and barrier properties [33] Proteins from anchovy by-products Improved mechanical, barrier, and surface properties [34] 3.…”
Section: Protein-based Film Type Mtgase Effect On the Films Referencesmentioning
confidence: 99%
“…Unmodified protein-based plastics, however, lack the mechanical properties and moisture resistance necessary for effective application in food packaging. It has been well observed that protein-based films are inherently brittle and exhibit poor barrier properties. …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, vegetable proteins are getting more attention in the development of biomaterials applicable to food packaging. ,, Due to the excellent biodegradability, abundance, lower cost, and inherent physicochemical characteristics determined by types of amino acids presented in the structure, soy protein biopolymers have already received much attention and demonstrated the potential for manufacturing of renewable plastics. , Soy protein possesses good film-forming capacity with great biocompatibility and offers better characteristics in terms of barrier properties against oxygen and aroma at low or intermediate relative humidity. However, the main disadvantages of soy protein-based films that need to be overcome are their high sensitivity to humidity and brittleness (lack of elasticity and, respectively, toughness). , Zein proteins, the main residue from the production of corn starch, are also shown to have promising physicochemical properties for the formation of films with good moisture and oxygen barrier performance, high glossiness, and strength .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, vegetable proteins are getting more attention in the development of biomaterials applicable to food packaging. 6,12,13 Due to the excellent biodegradability, abundance, lower cost, and inherent physicochemical characteristics determined by types of amino acids presented in the structure, soy protein biopolymers have already received much attention and demonstrated the potential for manufacturing of renewable plastics. 6,14 Soy protein possesses good film-forming capacity with great biocompatibility and offers better characteristics in terms of barrier properties against oxygen and aroma at low or intermediate relative humidity.…”
Section: ■ Introductionmentioning
confidence: 99%